Infestation of eyelashes by Pediculus humanus capitis (family: pediculidae): a case report - Madineh Abbasi; Saideh Yousefi (Journal of Medical Case Reports)
Abstract Background This case report describes a rare instance of Pediculus humanus capitis infestation affecting the eyelashes of a 10-year-old boy, notable for its ocular implications and unique diagnostic challenges. Case presentation In November 2023, a 10-year-old Iranian boy from East Azerbaijan Province, northwest Iran, presented to the ophthalmologist with symptoms that included itching, eyelash adhesions, redness, and swelling around the eyes, along with small yellow spots on the eyelashes. The ophthalmological examination revealed no visual defects. An eyelash sample collected for analysis confirmed the presence of lice eggs and nymphs; lice were also found on the scalp. The treatment included tetracycline ointment. By the third day, the nymphs had been eradicated, but lice eggs remained. The remaining lice eggs were subsequently removed using forceps. Conclusions This case underscores the importance of considering parasitic infestations in patients with ocular symptoms and highlights the associated public health and hygiene implications.